Single field inflationary models with non-compact Kaluza-Klein theory - Ledesma, D.S. (2004)
We discuss a semiclassical treatment to inflationary models from Kaluza-Klein theory without the cylinder condition. We conclude that the evolution of the early universe could be described by a geodesic trajectory of a cosmological 5D metric here proposed, so that the effective 4D FRW background metric should be a hypersurface on a constant fifth dimension. © 2003 Elsevier B.V. All rights reserved.